2017
DOI: 10.5812/jhealthscope.14148
|View full text |Cite
|
Sign up to set email alerts
|

Necessary Requirements for Implementation of Financial Reform in the Iranian Health Sector

Abstract: Background: A four-step map of financial reform in Iranian health sector has been proposed with the aim of increasing efficiency and resource allocation. Objectives: This study was conducted to investigate the necessary requirements to establish the three last phases of this reform in Iran, during year 2015. Methods: A qualitative study in the form of framework analysis approach was conducted. An interview guide was used for interviewing 22 purposefully selected experts individually in a semi-structured format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Conducting a part of the present duties of BOTs, particularly monitoring the performance of the university president as well as financial affairs, requires a permanent committee to change the university performance evaluation from the state of mere self-reporting by the university president ( 13 ). In this regard, the proposed committees, according to international experiences, include executive, budget and finance, buildings and lands, auditing, evaluation, human resources, development and public relations ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting a part of the present duties of BOTs, particularly monitoring the performance of the university president as well as financial affairs, requires a permanent committee to change the university performance evaluation from the state of mere self-reporting by the university president ( 13 ). In this regard, the proposed committees, according to international experiences, include executive, budget and finance, buildings and lands, auditing, evaluation, human resources, development and public relations ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…But legally, it has been clearly stipulated in BOTs law and BOTs have this right and responsibility ( 19 ). One of the most important needed actions is financial independence and universities should not be just financially dependent on the government ( 9 , 14 ). In this regard, enabling the option of donors’ aid is suggested as a means to increase the income of universities.…”
Section: Discussionmentioning
confidence: 99%
“…First, low participation may diminish health workers' trust when the decision-making process is not transparent and inclusive. The opacity of decision-making processes is one of the obstacles (16,17). Some studies also list nine evaluation criteria of public involvement in health resource allocation decision making, such as fair process and adequate opportunity for participation (18).…”
Section: Discussionmentioning
confidence: 99%
“…found that there were numerous problems with conducting financial reform despite spending a decade after its implementation in the Iranian health system. [ 5 ] Another study confirmed that fundamental changes need to be made to the accounting and financial reporting system of the Iranian health sector because of problems in the financial management system of the Iranian health sector. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%